2010
DOI: 10.1016/j.jmb.2010.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Characteristics of Rhinovirus Chimeras Designed in silico for En5hanced Presentation of HIV-1 gp41 Epitopes

Abstract: The development of an effective AIDS vaccine remains the most promising long-term strategy to combat human immunodeficiency virus (HIV)/AIDS. Here, we report favorable antigenic characteristics of vaccine candidates isolated from a combinatorial library of human rhinoviruses displaying the ELDKWA epitope of the gp41 glycoprotein of HIV-1. The design principles of this library emerged from the application of molecular modeling calculations in conjunction with our knowledge of previously obtained ELDKWA-displayi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…In an effort to produce live-virus immunogens capable of eliciting effective and cross-reactive immune responses against HIV-1, we have made a number of combinatorial libraries of chimeric viruses that display the conserved 2F5 epitope, E 662 LDKWA 667 [49,53], of the HIV-1 membrane-proximal external region (MPER; [35,42]; and this work). This region of the MPER appears to be flexible, normally assuming an extended structure in the N-terminal portion and a helical structure in the C-terminal portion, becoming more extended with β-turn conformations in the presence of 2F5 [31,43,44,54,55,56,57].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to produce live-virus immunogens capable of eliciting effective and cross-reactive immune responses against HIV-1, we have made a number of combinatorial libraries of chimeric viruses that display the conserved 2F5 epitope, E 662 LDKWA 667 [49,53], of the HIV-1 membrane-proximal external region (MPER; [35,42]; and this work). This region of the MPER appears to be flexible, normally assuming an extended structure in the N-terminal portion and a helical structure in the C-terminal portion, becoming more extended with β-turn conformations in the presence of 2F5 [31,43,44,54,55,56,57].…”
Section: Resultsmentioning
confidence: 99%
“…The pST-LIC plasmid was used for all of the genetic engineering. This plasmid was derived from modification of the previously used HRV-encoding p3IIST plasmid [47], whereby the sequences flanking the missing VP2 puff of the NIm-II region of HRV14 [48] were modified to have extended sticky ends to maximize the efficiency of ligation with complementary HIV-encoding DNA oligonucleotides [42]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in understanding of virus assembly have led to the development of methods that chemically and irreversibly inactivate whole virions and that maintain the receptor binding activity of Envelope (Arthur et al, 1998; Lifson et al, 2004). The attractiveness of VLPs that can mimic the natural HIV virion without any risk of HIV infection led to the early development of recombinant Gag-Env particles produced in mammalian cells by recombinant vaccinia virus (Haffar et al, 1990; Haffar et al, 1992; Haffar et al, 1991; Luo, Li, and Yong Kang, 2003), or rhinovirus chimeras (Arnold et al, 1994; Lapelosa et al, 2010), yeast (Tsunetsugu-Yokota et al, 2003), or in other systems, reviewed in (Deml et al, 2005). While clearly immunogenic in eliciting Gag-specific CTL (Paliard et al, 2000) and antibodies, including some neutralizing antibodies (Ding et al, 2002), none of these approaches has elicited strong protective immunity.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding reorganization free energy is recognized as an important component of the binding free energy 45 and a key factor needed to understand ligand affinity and specificity. 46 We have previously shown that conformational reorganization upon binding plays a pivotal role in cases, such as epitope-antibody binding, 47,48 in which there are small variations in the binding interface and most of the variations in binding affinities are due to differences in reorganization of the binding partners. Binding reorganization effects have been shown to be important in the FKBP12 system as well.…”
Section: Introductionmentioning
confidence: 99%